2009
DOI: 10.1203/pdr.0b013e3181a7b0a2
|View full text |Cite
|
Sign up to set email alerts
|

The B-cell Compartment in the Peripheral Blood of Children With Different Types of Primary Humoral Immunodeficiency

Abstract: ABSTRACT:The aim of this study was to evaluate the B-cell compartment in the peripheral blood of children with different types of hipogammaglobulinemia: common variable immunodeficiency (CVID), transient hypogammaglobulinemia of infancy (THI), and selective IgA deficiency (SIgAD). We analyzed by flow cytometry the changes in the B-cell subsets with age and showed that children with an early-onset CVID develop similar pattern of B-cell subsets as adult patients with CVID with age, as the levels of memory B cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
2
33
0
2
Order By: Relevance
“…They indicated a decrease in the frequency of switched memory cells, transitional cells as well as plasmablasts, and an increase in the CD21 low B cell subset compared to healthy individuals [53, 11]. In this sense, Celiksoy et al [51] demonstrated high counts of naive B cells in patients with SIgAD similar to CVID patients.…”
Section: Pathogenesis Of Sigadmentioning
confidence: 99%
“…They indicated a decrease in the frequency of switched memory cells, transitional cells as well as plasmablasts, and an increase in the CD21 low B cell subset compared to healthy individuals [53, 11]. In this sense, Celiksoy et al [51] demonstrated high counts of naive B cells in patients with SIgAD similar to CVID patients.…”
Section: Pathogenesis Of Sigadmentioning
confidence: 99%
“…However, several studies have demonstrated an association between levels of viremia in HIV-infected adults and B-cell death through increased expression of activation markers on B cells, such as bcl-2, LAIR-1, Fas and Fas-L [27,29,30,6265]. Increased activation-induced B-cell death is consistent with lower levels of CD27 + B cells in HIV-infected adults compared with uninfected adults [30,65].…”
Section: Effects Of Hiv On T and B Cells And Serologic Memorymentioning
confidence: 99%
“…Memory B cells can be further subdivided into marginal zone (MZ) B cells (CD19 + CD27 + IgM + IgD + ) and CSMB cells (CD19 + CD27 + IgM − IgD − ). The recirculating splenic MZ B cells synthesize IgM to a limited number of polysaccharide antigens without the help of T cells, while CSMB cells synthesize IgG, IgM and IgA in response to a wide variety of antigens with the help of follicular T cells …”
Section: Introductionmentioning
confidence: 99%